Airflow energy harvesting through diamagnetically levitated magnet rotor. (September 2019) - Gong, Qi; Su, Yufeng; Zhang, Kun; Wu, Kedi
Abstract: An airflow energy harvester by using diamagnetic levitation technology to generate electricity is presented in this paper. The energy harvester consists of a lifting magnet, an upper pyrolytic graphite plate, a magnet rotor, two centrosymmetric nozzles, induction coils, and a lower pyrolytic graphite plate. The lifting magnet is used to exert an upward force on the magnet rotor, so the levitated magnet rotor can stably levitate. In order to study the output characteristics of the energy harvester, two streams of airflow are applied to the magnet rotor to form a force couple. The relationship between the induced voltage and the airflow rate was analyzed and tested by simulation and experiment. In this paper, the flow rate was controlled by the mass flow controller, and the output voltage under different airflow rates was recorded. It was found that the peak induced voltage of the coil could reach 2.8 V when the flowrate was 3000 sccm.